2011
DOI: 10.1097/nen.0b013e318217d95f
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Prion Strains in a Transgenic Mouse Model Overexpressing Human A53T Mutated α-Synuclein

Abstract: There is a growing interest in the potential roles of misfolded protein interactions in neurodegeneration. To investigate this issue, we inoculated 3 prion strains intracerebrally into transgenic (TgM83) mice that overexpress human A53T α-synuclein. In comparison to nontransgenic controls, there was a striking decrease in the incubation periods of scrapie, classic and H-type bovine spongiform encephalopathies(C-BSE and H-BSE), with conservation of the histopathologic and biochemical features characterizing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 79 publications
4
30
0
Order By: Relevance
“…Using the PET blot method, we demonstrated that this pathologic form of >-synuclein is also PK resistant in the brain as well as in the gut. Using a panel of mice aged 1.5 to 22 months, we showed that pSer129 >-synuclein is not detected in the brains of young mice, in accordance with earlier observations (23), or in the ENS. More surprisingly, from as early as 5.5 months and up to 22 months of age, every TgM83 mouse analyzed showed aggregates of pSer129 >-synuclein in the brain and in the ENS in contrast to absence of any labeling in C57Bl/6 and C57Bl/6S control mice.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Using the PET blot method, we demonstrated that this pathologic form of >-synuclein is also PK resistant in the brain as well as in the gut. Using a panel of mice aged 1.5 to 22 months, we showed that pSer129 >-synuclein is not detected in the brains of young mice, in accordance with earlier observations (23), or in the ENS. More surprisingly, from as early as 5.5 months and up to 22 months of age, every TgM83 mouse analyzed showed aggregates of pSer129 >-synuclein in the brain and in the ENS in contrast to absence of any labeling in C57Bl/6 and C57Bl/6S control mice.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, diffuse perikaryal staining as well as spheroid-like inclusions in the enteric neurons were similar to those observed in neurons of the brains of this mouse model (21,23) and are comparable to those reported in enteric plexuses of PD patients (12,14,34Y36). Nevertheless, the labeling typically found in dystrophic neurites in the CNS was not easy to detect in the gut sections.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Injection of pre-formed α-Syn fibrils assembled in vitro into the brains of Tg mice bearing human mutant Tau also was used to demonstrate cross-seeding from α-Syn to Tau in vivo [110]. In other experiments, the inoculation of mouse-adapted scrapie strains intracerebrally into Tg mice that overexpress human α-Syn [111] or injection of heterotypic Aβ-seeded Tau in Tg mice (TauP301S) [44] was applied to study the interactions between these proteins. The inoculation of mouse-adapted PrP Sc into aged α-Syn Tg mice was used to prove that PrP Sc could promote α-Syn pathology [112].…”
Section: Methods For Investigation Of the Amyloid Interactomementioning
confidence: 99%
“…However, it is unclear to what extent they are self-propagating in a prion-like manner (220)(221)(222)(223)(224). In vivo studies of intracerebral injections of aggregated α-synuclein in transgene animal models with α-synuclein mutations have further shown accelerated occurrence of protein aggregation, followed by nigral loss and motor deficits, not present to the similar extent in wild type (WT) animals (225)(226)(227). Thus, exogenous seeds of α-synuclein may accelerate the pathogenesis of a genetically predisposed α-synuclein aggregation disease.…”
Section: Pd As a Prion Diseasementioning
confidence: 99%